A solar photovoltaic module and a method of manufacturing the same

CN116825887BActive Publication Date: 2026-10-27ECONESS ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310623940.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2026-10-27
Estimated Expiration
2043-05-30

AI Technical Summary

Technical Problem

但是,由薄膜制成的光伏组件在长时间的使用过程中因高温、紫外的影响容易出现黄变的现象,影响光伏组件的透光率

Benefits of technology

[0019](1)本发明的柔性透光层为PET膜,使得光伏组件不仅透光度好、质量轻、而且耐磨性好,可以有效保护电池片。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of photovoltaic module, in particular to a solar photovoltaic module and a preparation method thereof.The flexible light-transmitting layer of the present application is PET film, so that the photovoltaic module has good light transmittance, light weight and good wear resistance, and can effectively protect the battery piece.The present application provides a preparation method of polyvinyl butyral resin, and a PVB adhesive film for upper and lower adhesive layers is prepared based on the polyvinyl butyral resin.The PVB adhesive film has good transparency and adhesion, so that the adhesion is firm and the quality is light.Titanium dioxide powder has certain heat insulation performance, but a high content will seriously affect the visible light transmittance of the film, therefore, the present application adds titanium dioxide microcapsules in the PVB adhesive film, so as to further improve the dispersion performance and ultraviolet resistance of nano titanium dioxide, and alleviate the agglomeration of titanium dioxide powder in the PVB adhesive film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photovoltaic module technology, specifically to a solar photovoltaic module and its preparation method. Background Technology

[0002] With the development of photovoltaic technology, portable photovoltaic modules are becoming increasingly popular. However, the application of crystalline silicon solar modules based on crystalline silicon technology is limited by the fragility of their cells. In recent years, the development technology of flexible batteries has matured, and their advantages of being resistant to deformation and breakage have made them popular in the portable market.

[0003] Conventional solar cells typically consist of two layers of glass with EVA material and the solar cell sandwiched in between. Such modules are relatively heavy, require supports for installation, and are not easily moved. Flexible thin-film solar cells, on the other hand, do not require a glass backsheet or cover plate, making them 80% lighter than double-glass solar cell modules. Flexible cells using a PVC backsheet and ETFE film cover plate can even be bent arbitrarily, making them easy to carry. This will greatly promote the application of solar energy, making it possible to shape solar cells into any form and attach them to any surface. This represents a new technological revolution with broad market prospects. However, photovoltaic modules made of thin film are prone to yellowing due to high temperatures and ultraviolet radiation during prolonged use, affecting their light transmittance.

[0004] To address the aforementioned issues and improve the light transmittance and UV resistance of photovoltaic modules, this invention provides a solar photovoltaic module and its preparation method. Summary of the Invention

[0005] The purpose of this invention is to provide a solar photovoltaic module and its preparation method to solve the problems mentioned in the background art.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0007] A method for preparing a solar photovoltaic module, wherein the method comprises: stacking a flexible light-transmitting layer, an upper adhesive layer, a solar cell layer, a lower adhesive layer, and a backsheet layer sequentially from top to bottom, hot-pressing at 140-150℃ for 15-20 minutes, and cooling to obtain a solar photovoltaic module;

[0008] The flexible light-transmitting layer is a PET film;

[0009] Both the upper adhesive layer and the lower adhesive layer are PVB films.

[0010] The solar cell layer is a heterojunction solar cell.

[0011] The backplane layer is a flexible PCB board.

[0012] A more optimized method for preparing the PVB film is as follows: taking polyvinyl butyral resin, titanium dioxide microcapsules, bismaleimide, trimethylolpropane trimethacrylate, aminosilane coupling agent, and plasticizer, mixing them evenly, melting and extruding, irradiating, rolling, and cutting to obtain the PVB film.

[0013] In a more optimized manner, the PVB film comprises the following components by weight: 85-110 parts polyvinyl butyral resin, 6-8 parts titanium dioxide microcapsules, 4-5 parts bismaleimide, 2-3 parts trimethylolpropane trimethacrylate, 4-6 parts coupling agent, and 20-25 parts plasticizer.

[0014] More preferably, the plasticizer is dioctyl phthalate; and the coupling agent is an aminosilane coupling agent.

[0015] A more optimized method for preparing the titanium dioxide microcapsules is as follows: sorbitol monooleate, dodecylphenol polyoxyethylene ether, and thiolated hyaluronic acid are taken and stirred evenly to obtain an emulsified aqueous solution; titanium dioxide and isooctane solvent are taken and stirred evenly to obtain an organic solution; tetradecane and methyl methacrylate are taken and stirred evenly, added to the organic solution, stirred evenly to obtain an oil phase; the oil phase is added to the emulsified aqueous solution, ultrasonically dispersed, heated to 60-65℃, ammonium persulfate is added dropwise, the reaction is carried out for 4-6 hours, dialyzed, and freeze-dried to obtain titanium dioxide microcapsules.

[0016] A more optimized method for preparing the thiolized hyaluronic acid is as follows: hyaluronic acid and deionized water are taken, stirred evenly, diimine hydrochloride and N-hydroxysuccinimide are added, HCl is added to adjust the pH value to 4-5, the reaction is carried out for 50-60 min, cystamine dihydrochloride is added, the reaction is carried out for 46-50 h, dialyzed, sodium hydroxide is added, the pH value is adjusted to 7.5-8, DL-dithiothreitol is added, the reaction is carried out in a nitrogen atmosphere in the dark for 22-26 h, dialyzed, and freeze-dried to obtain thiolized hyaluronic acid.

[0017] A more optimized method for preparing the polyvinyl butyral resin is as follows: Polyvinyl alcohol and deionized water are heated to 95-100℃, stirred until homogeneous, filtered, cooled to 40-45℃, n-butyraldehyde is added, and stirred for 30-40 minutes to obtain a mixed solution. The solution is then cooled to 35-36℃, hydrochloric acid aqueous solution is added, and stirred for 1-2 hours. Hydrochloric acid aqueous solution is added again, the temperature is raised to 55-60℃, and the reaction is carried out for 2.5-3.5 hours. The solution is cooled to 50-55℃, sodium hydroxide solution is added, and the pH value is adjusted to 4. The solution is then filtered, washed, and then further filtered, washed, and dried to obtain the polyvinyl butyral resin.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] (1) The flexible light-transmitting layer of the present invention is a PET film, which makes the photovoltaic module not only have good light transmittance and light weight, but also good wear resistance, which can effectively protect the battery cells.

[0020] (2) This invention provides a method for preparing polyvinyl butyral resin, and based on this method, prepares a PVB film for the upper and lower adhesive layers. This PVB film has good transparency and adhesion, resulting in strong adhesion and light weight. Titanium dioxide powder has certain heat insulation properties, but excessive content will seriously affect the visible light transmittance of the film. Therefore, this invention adds titanium dioxide microcapsules to the PVB film, which can further improve the dispersion performance and UV resistance of nano-titanium dioxide, and alleviate the agglomeration of titanium dioxide powder in the PVB film.

[0021] This invention prepares a microcapsule material with titanium dioxide as the core material, and adds tetradecane as a vaporizing agent. The tetradecane is vaporized by high-energy rays, causing the microcapsules to burst, so that the titanium dioxide is evenly dispersed in the PVB film, improving the dispersibility of titanium dioxide and enhancing the UV resistance of the PVB film.

[0022] This invention prepares a microcapsule material with thiolized hyaluronic acid as one of the shell materials. Thiolized hyaluronic acid has good light transmittance, and the addition of thiolized hyaluronic acid can enhance the light transmittance of the upper and lower adhesive layers.

[0023] This invention adds bismaleimide to the PVB film. The thiol groups on the thiolized hyaluronic acid can be covalently linked to the maleimide groups on the bismaleimide, thus cross-linking and improving the tensile strength and service life of the PVB film. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] The main sources of materials used in this invention are as follows:

[0026] The PET film, 0.15mm thick, model DELS-UV-200-B release liner, is supplied by DELS.

[0027] Polyvinyl alcohol: Model: 17-99, provided by Anhui Wanwei High-Tech Materials Co., Ltd.

[0028] Bismaleimide: Model 5260, supplied by Cytec.

[0029] Trimethylolpropane trimethacrylate: Product No.: 246840-100G, provided by Sigma-Aldrich Shanghai Trading Co., Ltd.

[0030] Aminosilane coupling agent: Product No.: KH-602, provided by Guangzhou Zhongjie New Materials Co., Ltd.

[0031] Dioctyl phthalate: Product No.: N0033, provided by Sigma-Aldrich Shanghai Trading Co., Ltd.

[0032] Hyaluronic acid: Product number: 700159P-5MG, provided by Hubei Nuona Technology Co., Ltd.

[0033] Nano titanium dioxide, particle size: 20nm.

[0034] Example 1:

[0035] Step 1: Preparation of polyvinyl butyral resin:

[0036] Take 100g of polyvinyl alcohol and 1000g of deionized water, heat to 98℃, stir evenly, filter, cool to 42℃, add 52g of n-butyraldehyde, stir for 35min to obtain a mixed solution, cool to 35℃, add 47g of 1.0% hydrochloric acid aqueous solution, stir for 1.5h, add 8g of 1.0% hydrochloric acid aqueous solution, heat to 57℃, react for 3h, cool to 52℃, add sodium hydroxide solution, adjust the pH value to 4, filter, wash, add sodium hydroxide solution, adjust the pH value to 12, filter, wash, and dry to obtain polyvinyl butyral resin.

[0037] Step 2: Preparation of thiolated hyaluronic acid:

[0038] Take 0.5g of hyaluronic acid and 50mL of deionized water, stir well, add 1g of diimine hydrochloride and 0.55g of N-hydroxysuccinimide, add HCl to adjust the pH to 4, react for 55min, add 0.9g of cystamine dihydrochloride, react for 50h, dialyze, add sodium hydroxide, adjust the pH to 7.5, add 2.4g of DL-dithiothreitol, react in the dark under a nitrogen atmosphere for 24h, dialyze, freeze dry to obtain thiolized hyaluronic acid.

[0039] Step 3: Preparation of titanium dioxide microcapsules:

[0040] Take 1.5g of sorbitan monooleate, 3.5g of dodecylphenol polyoxyethylene ether, and 1g of mercapto-modified hyaluronic acid, stir well to obtain an emulsified aqueous solution;

[0041] Take 8g of titanium dioxide and 15g of isooctane solvent, stir well to obtain an organic solution;

[0042] Take 4g of tetradecane and 35g of methyl methacrylate, stir evenly, add organic solution, stir evenly to obtain oil phase, add oil phase to emulsified aqueous solution, ultrasonically disperse for 6min, heat to 62℃, add 0.5g of ammonium persulfate dropwise, react for 5h, dialyze for 24h to remove unreacted reaction aids or solvents, freeze dry to obtain titanium dioxide microcapsules.

[0043] Step 4: Preparation of PVB film:

[0044] Polyvinyl butyral resin, titanium dioxide microcapsules, bismaleimide, trimethylolpropane trimethacrylate, aminosilane coupling agent, and plasticizer were mixed evenly, melted and extruded, and irradiated using an electron accelerator with an electron beam of 10 MeV, a beam current of 60 mA, and a rated power of 100 kW. The mixture was then rolled and cut to obtain a PVB film with dimensions of 2100 mm × 1050 mm × 0.8 mm.

[0045] The PVB adhesive comprises the following components by weight: 100 parts polyvinyl butyral resin, 7 parts modified titanium dioxide microcapsules, 4.5 parts bismaleimide, 2.5 parts trimethylolpropane trimethacrylate, 5 parts aminosilane coupling agent, and 23 parts plasticizer.

[0046] Step 5: Preparation of solar photovoltaic modules:

[0047] The flexible light-transmitting layer, the upper adhesive layer, the solar cell layer, the lower adhesive layer, and the backsheet layer are stacked sequentially from top to bottom, hot-pressed at 145℃ for 17 minutes, and then cooled to obtain a solar photovoltaic module.

[0048] Example 2:

[0049] Step 1: Preparation of polyvinyl butyral resin:

[0050] Take 100g of polyvinyl alcohol and 1000g of deionized water, heat to 95℃, stir evenly, filter, cool to 40℃, add 52g of n-butyraldehyde, stir for 30min to obtain a mixed solution, cool to 35℃, add 47g of 1.0% hydrochloric acid aqueous solution, stir for 1h, add 8g of 1.0% hydrochloric acid aqueous solution, heat to 55℃, react for 2.5h, cool to 50℃, add sodium hydroxide solution, adjust the pH value to 4, filter, wash, add sodium hydroxide solution, adjust the pH value to 12, filter, wash, and dry to obtain polyvinyl butyral resin.

[0051] Step 2: Preparation of thiolated hyaluronic acid:

[0052] Take 0.5g of hyaluronic acid and 50mL of deionized water, stir well, add 1g of diimine hydrochloride and 0.55g of N-hydroxysuccinimide, add HCl to adjust the pH to 4, react for 50min, add 0.9g of cystamine dihydrochloride, react for 46h, dialyze, add sodium hydroxide, adjust the pH to 7.5, add 2.4g of DL-dithiothreitol, react in the dark under a nitrogen atmosphere for 22h, dialyze, freeze dry to obtain thiolized hyaluronic acid.

[0053] Step 3: Preparation of titanium dioxide microcapsules:

[0054] Take 1.5g of sorbitan monooleate, 3.5g of dodecylphenol polyoxyethylene ether, and 1g of mercapto-modified hyaluronic acid, stir well to obtain an emulsified aqueous solution;

[0055] Take 8g of titanium dioxide and 15g of isooctane solvent, stir well to obtain an organic solution;

[0056] Take 4g of tetradecane and 35g of methyl methacrylate, stir evenly, add organic solution, stir evenly to obtain oil phase, add oil phase to emulsified aqueous solution, ultrasonically disperse for 5min, heat to 60℃, add 0.5g of ammonium persulfate dropwise, react for 4h, dialyze for 22h to remove unreacted reaction aids or solvents, freeze dry to obtain titanium dioxide microcapsules.

[0057] Step 4: Preparation of PVB film:

[0058] Polyvinyl butyral resin, titanium dioxide microcapsules, bismaleimide, trimethylolpropane trimethacrylate, aminosilane coupling agent, and plasticizer were mixed evenly, melted and extruded, and irradiated using an electron accelerator with an electron beam of 10 MeV and a beam current of 60 mA. The mixture was then rolled and cut to obtain a PVB film with a size of 2100 mm × 1050 mm × 0.8 mm.

[0059] The PVB adhesive comprises the following components by weight: 85 parts polyvinyl butyral resin, 6 parts modified titanium dioxide microcapsules, 4 parts bismaleimide, 2 parts trimethylolpropane trimethacrylate, 4 parts aminosilane coupling agent, and 20 parts plasticizer.

[0060] Step 5: Preparation of solar photovoltaic modules:

[0061] The flexible light-transmitting layer, the upper adhesive layer, the solar cell layer, the lower adhesive layer, and the backsheet layer are stacked sequentially from top to bottom, hot-pressed at 140℃ for 15 minutes, and then cooled to obtain a solar photovoltaic module.

[0062] Example 3:

[0063] Step 1: Preparation of polyvinyl butyral resin:

[0064] Take 100g of polyvinyl alcohol and 1000g of deionized water, heat to 100℃, stir evenly, filter, cool to 45℃, add 52g of n-butyraldehyde, stir for 40min to obtain a mixed solution, cool to 36℃, add 47g of 1.0% hydrochloric acid aqueous solution, stir for 2h, add 8g of 1.0% hydrochloric acid aqueous solution, heat to 60℃, react for 3.5h, cool to 55℃, add sodium hydroxide solution, adjust the pH value to 4, filter, wash, add sodium hydroxide solution, adjust the pH value to 12, filter, wash, and dry to obtain polyvinyl butyral resin.

[0065] Step 2: Preparation of thiolated hyaluronic acid:

[0066] Take 0.5g of hyaluronic acid and 50mL of deionized water, stir well, add 1g of diimine hydrochloride and 0.55g of N-hydroxysuccinimide, add HCl to adjust the pH to 5, react for 60min, add 0.9g of cystamine dihydrochloride, react for 50h, dialyze, add sodium hydroxide, adjust the pH to 8, add 2.4g of DL-dithiothreitol, react in the dark under a nitrogen atmosphere for 26h, dialyze and freeze dry to obtain thiolized hyaluronic acid.

[0067] Step 3: Preparation of titanium dioxide microcapsules:

[0068] Take 1.5g of sorbitan monooleate, 3.5g of dodecylphenol polyoxyethylene ether, and 1g of mercapto-modified hyaluronic acid, stir well to obtain an emulsified aqueous solution;

[0069] Take 8g of titanium dioxide and 15g of isooctane solvent, stir well to obtain an organic solution;

[0070] Take 4g of tetradecane and 35g of methyl methacrylate, stir evenly, add organic solution, stir evenly to obtain oil phase, add oil phase to emulsified aqueous solution, ultrasonically disperse for 8min, heat to 65℃, add 0.5g of ammonium persulfate dropwise, react for 6h, dialyze for 26h to remove unreacted reaction aids or solvents, freeze dry to obtain titanium dioxide microcapsules.

[0071] Step 4: Preparation of PVB film:

[0072] Polyvinyl butyral resin, titanium dioxide microcapsules, bismaleimide, trimethylolpropane trimethacrylate, aminosilane coupling agent, and plasticizer were mixed evenly, melted and extruded, and irradiated using an electron accelerator with an electron beam of 10 MeV and a beam current of 60 mA. The mixture was then rolled and cut to obtain a PVB film with a size of 2100 mm × 1050 mm × 0.8 mm.

[0073] The PVB adhesive comprises the following components by weight: 110 parts polyvinyl butyral resin, 8 parts modified titanium dioxide microcapsules, 5 parts bismaleimide, 3 parts trimethylolpropane trimethacrylate, 6 parts aminosilane coupling agent, and 25 parts plasticizer.

[0074] Step 5: Preparation of solar photovoltaic modules:

[0075] The flexible light-transmitting layer, the upper adhesive layer, the solar cell layer, the lower adhesive layer, and the backsheet layer are stacked sequentially from top to bottom, hot-pressed at 150°C for 20 minutes, and then cooled to obtain a solar photovoltaic module.

[0076] Comparative Example 1: Titanium dioxide was not prepared into microcapsules, but otherwise the same as in Example 1.

[0077] Step 1: Preparation of polyvinyl butyral resin:

[0078] Take 100g of polyvinyl alcohol and 1000g of deionized water, heat to 98℃, stir evenly, filter, cool to 42℃, add 52g of n-butyraldehyde, stir for 35min to obtain a mixed solution, cool to 35℃, add 47g of 1.0% hydrochloric acid aqueous solution, stir for 1.5h, add 8g of 1.0% hydrochloric acid aqueous solution, heat to 57℃, react for 3h, cool to 52℃, add sodium hydroxide solution, adjust the pH value to 4, filter, wash, add sodium hydroxide solution, adjust the pH value to 12, filter, wash, and dry to obtain polyvinyl butyral resin.

[0079] Step 2: Preparation of thiolated hyaluronic acid:

[0080] Take 0.5g of hyaluronic acid and 50mL of deionized water, stir well, add 1g of diimine hydrochloride and 0.55g of N-hydroxysuccinimide, add HCl to adjust the pH to 4, react for 55min, add 0.9g of cystamine dihydrochloride, react for 50h, dialyze, add sodium hydroxide, adjust the pH to 7.5, add 2.4g of DL-dithiothreitol, react in the dark under a nitrogen atmosphere for 24h, dialyze, freeze dry to obtain thiolized hyaluronic acid.

[0081] Step 3: Preparation of titanium dioxide microcapsules:

[0082] Take 1.5g of sorbitan monooleate, 3.5g of dodecylphenol polyoxyethylene ether, and 1g of mercapto-modified hyaluronic acid, stir well to obtain an emulsified aqueous solution;

[0083] Take 8g of titanium dioxide and 15g of isooctane solvent, stir well to obtain an organic solution;

[0084] Take 4g of tetradecane and 35g of methyl methacrylate, stir evenly, add organic solution, stir evenly to obtain oil phase, add oil phase to emulsified aqueous solution, ultrasonically disperse for 6min, heat to 62℃, add 0.5g of ammonium persulfate dropwise, react for 5h, dialyze for 24h to remove unreacted reaction aids or solvents, freeze dry to obtain titanium dioxide microcapsules.

[0085] Step 4: Preparation of PVB film:

[0086] Polyvinyl butyral resin, titanium dioxide microcapsules, bismaleimide, trimethylolpropane trimethacrylate, aminosilane coupling agent, and plasticizer were mixed evenly, melted and extruded, and irradiated using an electron accelerator with an electron beam of 10 MeV and a beam current of 60 mA. The mixture was then rolled and cut to obtain a PVB film with a size of 2100 mm × 1050 mm × 0.8 mm.

[0087] The PVB adhesive comprises the following components by weight: 100 parts polyvinyl butyral resin, 7 parts modified titanium dioxide microcapsules, 4.5 parts bismaleimide, 2.5 parts trimethylolpropane trimethacrylate, 5 parts aminosilane coupling agent, and 23 parts plasticizer.

[0088] Step 5: Preparation of solar photovoltaic modules:

[0089] The flexible light-transmitting layer, the upper adhesive layer, the solar cell layer, the lower adhesive layer, and the backsheet layer are stacked sequentially from top to bottom, hot-pressed at 145℃ for 17 minutes, and then cooled to obtain a solar photovoltaic module.

[0090] Comparative Example 2: Thiol-modified hyaluronic acid was not added to the titanium dioxide microcapsules; otherwise, it was the same as in Example 1.

[0091] Step 1: Preparation of polyvinyl butyral resin:

[0092] Take 100g of polyvinyl alcohol and 1000g of deionized water, heat to 98℃, stir evenly, filter, cool to 42℃, add 52g of n-butyraldehyde, stir for 35min to obtain a mixed solution, cool to 35℃, add 47g of 1.0% hydrochloric acid aqueous solution, stir for 1.5h, add 8g of 1.0% hydrochloric acid aqueous solution, heat to 57℃, react for 3h, cool to 52℃, add sodium hydroxide solution, adjust the pH value to 4, filter, wash, add sodium hydroxide solution, adjust the pH value to 12, filter, wash, and dry to obtain polyvinyl butyral resin.

[0093] Step 2: Preparation of thiolated hyaluronic acid:

[0094] Take 0.5g of hyaluronic acid and 50mL of deionized water, stir well, add 1g of diimine hydrochloride and 0.55g of N-hydroxysuccinimide, add HCl to adjust the pH to 4, react for 55min, add 0.9g of cystamine dihydrochloride, react for 50h, dialyze, add sodium hydroxide, adjust the pH to 7.5, add 2.4g of DL-dithiothreitol, react in the dark under a nitrogen atmosphere for 24h, dialyze, freeze dry to obtain thiolized hyaluronic acid.

[0095] Step 3: Preparation of titanium dioxide microcapsules:

[0096] Take 1.5g of sorbitan monooleate, 3.5g of dodecylphenol polyoxyethylene ether, and 1g of mercapto-modified hyaluronic acid, stir well to obtain an emulsified aqueous solution;

[0097] Take 8g of titanium dioxide and 15g of isooctane solvent, stir well to obtain an organic solution;

[0098] Take 4g of tetradecane and 35g of methyl methacrylate, stir evenly, add organic solution, stir evenly to obtain oil phase, add oil phase to emulsified aqueous solution, ultrasonically disperse for 6min, heat to 62℃, add 0.5g of ammonium persulfate dropwise, react for 5h, dialyze for 24h to remove unreacted reaction aids or solvents, freeze dry to obtain titanium dioxide microcapsules.

[0099] Step 4: Preparation of PVB film:

[0100] Polyvinyl butyral resin, titanium dioxide microcapsules, bismaleimide, trimethylolpropane trimethacrylate, aminosilane coupling agent, and plasticizer were mixed evenly, melted and extruded, and irradiated using an electron accelerator with an electron beam of 10 MeV and a beam current of 60 mA. The mixture was then rolled and cut to obtain a PVB film with a size of 2100 mm × 1050 mm × 0.8 mm.

[0101] The PVB adhesive comprises the following components by weight: 100 parts polyvinyl butyral resin, 7 parts modified titanium dioxide microcapsules, 4.5 parts bismaleimide, 2.5 parts trimethylolpropane trimethacrylate, 5 parts aminosilane coupling agent, and 23 parts plasticizer.

[0102] Step 5: Preparation of solar photovoltaic modules:

[0103] The flexible light-transmitting layer, the upper adhesive layer, the solar cell layer, the lower adhesive layer, and the backsheet layer are stacked sequentially from top to bottom, hot-pressed at 145℃ for 17 minutes, and then cooled to obtain a solar photovoltaic module.

[0104] experiment:

[0105] The performance of the solar photovoltaic modules prepared in Examples 1-3 and Comparative Examples 1-2 was tested. According to GB / T14522-2008, the UV aging performance of the PVB films in Examples 1-3 and Comparative Examples 1-2 was tested, with a UV irradiation time of 1000 hours. The light transmittance of the PVB films after UV aging was tested. According to GB / T 528-2009, the tensile strength of the PVB films in Examples 1-3 and Comparative Examples 1-2 was tested, and the data are shown in the table below.

[0106] Example 1 92.6 29.1 Example 2 92.9 29.4 Example 3 92.7 29.2 Comparative Example 1 85.3 27.6 Comparative Example 2 88.1 24.7

[0107] Conclusion: In Comparative Example 1, titanium dioxide was not prepared into microcapsules, which made it easy for titanium dioxide to agglomerate in the PVB film, affecting the UV resistance of the PVB film and significantly reducing the light transmittance after UV aging. In Comparative Example 2, no thiolized hyaluronic acid was added to the titanium dioxide microcapsules, resulting in a decrease in light transmittance. At the same time, the bismaleimide in Comparative Example 2 could not crosslink with the thiol groups on the thiolized hyaluronic acid, which significantly reduced the tensile strength of the film.

[0108] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a solar photovoltaic module, characterized in that: The method for preparing the solar photovoltaic module is as follows: the flexible light-transmitting layer, the upper adhesive layer, the solar cell layer, the lower adhesive layer, and the backsheet layer are stacked sequentially from top to bottom, hot-pressed at 140-150℃ for 15-20 minutes, and then cooled to obtain the solar photovoltaic module. The flexible light-transmitting layer is a PET film; Both the upper adhesive layer and the lower adhesive layer are PVB films. The solar cell layer is a heterojunction solar cell. The backplane layer is a flexible PCB board; The preparation method of the PVB film is as follows: take polyvinyl butyral resin, titanium dioxide microcapsules, bismaleimide, trimethylolpropane trimethacrylate, aminosilane coupling agent, and plasticizer, mix them evenly, melt and extrude, irradiate, roll and cut to obtain the PVB film. The preparation method of the titanium dioxide microcapsules is as follows: Sorbitol monooleate, dodecylphenol polyoxyethylene ether, and thiolated hyaluronic acid are taken and stirred evenly to obtain an emulsified aqueous solution; titanium dioxide and isooctane solvent are taken and stirred evenly to obtain an organic solution; tetradecane and methyl methacrylate are taken and stirred evenly, added to the organic solution, stirred evenly to obtain an oil phase, the oil phase is added to the emulsified aqueous solution, ultrasonically dispersed, heated to 60-65℃, ammonium persulfate is added dropwise, reacted for 4-6 hours, dialyzed, and freeze-dried to obtain titanium dioxide microcapsules.

2. The method for preparing a solar photovoltaic module according to claim 1, characterized in that: The PVB film comprises the following components by weight: 85-110 parts polyvinyl butyral resin, 6-8 parts titanium dioxide microcapsules, 4-5 parts bismaleimide, 2-3 parts trimethylolpropane trimethacrylate, 4-6 parts coupling agent, and 20-25 parts plasticizer.

3. The method for preparing a solar photovoltaic module according to claim 1, characterized in that: The plasticizer is dioctyl phthalate; the coupling agent is an aminosilane coupling agent.

4. The method for preparing a solar photovoltaic module according to claim 1, characterized in that: The preparation method of the thiolized hyaluronic acid is as follows: take hyaluronic acid and deionized water, stir evenly, add diimine hydrochloride and N-hydroxysuccinimide, add HCl to adjust the pH value to 4-5, react for 50-60 min, add cystamine dihydrochloride, react for 46-50 h, dialyze, add sodium hydroxide, adjust the pH value to 7.5-8, add DL-dithiothreitol, react in the dark under a nitrogen atmosphere for 22-26 h, dialyze, freeze dry to obtain thiolized hyaluronic acid.

5. The method for preparing a solar photovoltaic module according to claim 1, characterized in that: The preparation method of the polyvinyl butyral resin is as follows: take polyvinyl alcohol and deionized water, heat to 95-100℃, stir evenly, filter, cool to 40-45℃, add n-butyraldehyde, stir for 30-40 min to obtain a mixed solution, cool to 35-36℃, add hydrochloric acid aqueous solution, stir for 1-2 h, add hydrochloric acid aqueous solution, heat to 55-60℃, react for 2.5-3.5 h, cool to 50-55℃, add sodium hydroxide solution, adjust the pH value to 4, filter and wash, add sodium hydroxide solution, adjust the pH value to 12, filter, wash and dry to obtain polyvinyl butyral resin.

6. A solar photovoltaic module prepared by the method of preparing a solar photovoltaic module according to any one of claims 1-5.

Citation Information

Patent Citations

  • Flexible solar battery pack and preparation method thereof

    CN101702412A

  • Transparent heat-insulating anti-ultraviolet nanocomposite sheet and preparation method thereof

    CN108864625A